Association Between Physical Activity, Quadriceps Muscle Performance, and Biological Characteristics of Very Old Men and Women. Issue 1 (18th August 2021) - Varesco, Giorgio; Coudy-Gandilhon, Cécile; Lapole, Thomas; Decourt, Alice; Gueugneau, Marine; Barthélémy, Jean-Claude; Roche, Frédéric; Bechet, Daniel; Féasson, Léonard; Rozand, Vianney
Abstract: The aim of the study was to evaluate the association between physical activity, knee extensors (KE) performance (ie, isometric strength and fatigability), and biological parameters (ie, muscle structural, microvascular, and metabolic properties) in healthy very old men and women. Thirty very old adults (82 ± 1 years, 15 women) performed an isometric Quadriceps Intermittent Fatigue (QIF) test for the assessment of KE maximal force, total work (index of absolute performance), and fatigability. Muscle biopsies from the vastus lateralis muscle were collected to assess muscle fibers type and morphology, microvasculature, and enzymes activity. Correlation analyses were used to investigate the relationships between physical activity (steps/day, actimetry), KE performance, and biological data for each sex separately. Men, compared to women, showed greater total work at the QIF test (44 497 ± 8 629 Ns vs 26 946 ± 4 707 Ns; p < .001). Steps per day were correlated with total work only for women ( r = 0.73, p = .011). In men, steps per day were correlated with the percentage ( r = 0.57, p = .033), shape factor ( r = 0.75, p = .002), and capillary tortuosity of type IIX fibers ( r = 0.59, p = .035). No other relevant correlations were observed for men or women between steps per day and biological parameters. Physical activity level was positively associated with the capacity of very old women to perform a fatiguing test, but not maximal force production capacity of the KE. Physical activity of very old men was not correlated with muscle performance. We suggest that very old women could be at higher risk of autonomy loss and increasing the steps per day count could provide a sufficient stimulus for adaptations in less active women.